Condition monitoring techniques for electrical equipment-a literature survey. - Han, Y.
Increasing interest has been seen in condition monitoring (CM) techniques for electrical equipment, mainly including transformer, generator, and induction motor in power plants, because CM has the potential to reduce operating costs, enhance the reliability of operation, and improve power supply and service to customers. Literatures are accumulated on developing intelligent CM systems with advanced practicability, sensitivity, reliability and automation. A literature survey is felt necessary with an aim to reflect the state of the art development in this important area. After introducing the concepts and functions of CM, this paper describes the popular monitoring methods for and research status of CM on transformer, generator, and induction motor, respectively. The paper also points out the potential benefits through the utilization of advanced signal processing and artificial intelligence techniques in developing novel CM schemes.
Keywords: Advanced signal processing; Artificial intelligence techniques; Condition monitoring techniques; Electrical equipment; Generators; Induction motors; Literature survey; State of the art; Transformers